The Bricks We Lay: Pursuing a Plague Genome from First Pandemic Turkey and the Realities of Ancient DNA - Manalo, Ren (My University, 2024)
Conclusive genomic and historical analysis of the first plague pandemic is remarkably diminutive due to a lack of associated archaeological evidence. Genomic research has established the presence of Yersinia pestis in Central Asia during the late 2nd century, as well as in England, France, Germany, and Spain in the 6th through 8th centuries. Considering the state of the scholarship that uses written sources to construct plague’s history, the first pandemic’s debated transmission from Central Asia towards the Mediterranean, demands further scientific analysis and careful interdisciplinary contextualization. As stressed in the historiography, a central region in the history of the first plague pandemic is Turkey, though there is not yet any genomic evidence that places first-pandemic plague there. This study analyzed 134 human teeth from sites in northern and northwestern Turkey in efforts to derive the first Northeastern Mediterranean Y. pestis genome for the first plague pandemic. The study successfully identified one individual who died with detectable levels of Yersinia pestis in their bloodstream; this individual will later undergo enrichment to increase the pathogenic portion of the extract. One individual demonstrated significant levels of hepatitis B virus and other individuals had detectable levels of Mycobacterium tuberculosis. All the remains yielded very little endogenous content indicating poor overall preservation. Plague studies have been historically defined by a system created to generate and answer primarily Eurocentric questions. Although a single novel genome from Turkey cannot completely answer the many debates associated with the first plague pandemic, it does alter the geography of current Y. pestis discoveries which remain restricted to western European sites. It would also serve to highlight the necessity for a wider geographic sampling range and more interdisciplinary analysis. This study also comments on the understated realities of ancient DNA and the necessity for a push in ethical decision-making in the field.
Keywords: anthropology; ancient DNA; plague; Turkey; pandemic